2005
DOI: 10.1099/mic.0.28137-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-encoded gene cluster for the metabolic pathway that converts aniline to TCA-cycle intermediates in Delftia tsuruhatensis AD9

Abstract: Delftia tsuruhatensis AD9 was isolated as an aniline-degrading bacterium from the soil surrounding a textile dyeing plant. The gene cluster involved in aniline degradation was cloned from the total DNA of strain AD9 into Escherichia coli JM109. After shotgun cloning, two recombinant E. coli strains showing aniline oxidation activity or catechol meta-cleavage activity were obtained by simple plate assays. These strains contained 9?3 kb and 15?4 kb DNA fragments, respectively. Sequence analysis of the total 24?7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 54 publications
3
63
0
2
Order By: Relevance
“…2). Catechols are known to be the oxidation products from aniline, methylaniline, and chloroaniline (14,18,32,33), but this is the first report to have detected a major amount of catechol from aniline. Next, to prove the presence of ␥-glutamyl intermediates in aniline oxidation, we purified the GS-like protein AtdA1 and showed that it can produce ␥-GA from aniline and L-glutamate in the presence of ATP and MgCl 2 (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…2). Catechols are known to be the oxidation products from aniline, methylaniline, and chloroaniline (14,18,32,33), but this is the first report to have detected a major amount of catechol from aniline. Next, to prove the presence of ␥-glutamyl intermediates in aniline oxidation, we purified the GS-like protein AtdA1 and showed that it can produce ␥-GA from aniline and L-glutamate in the presence of ATP and MgCl 2 (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…To date, several AD genes have been cloned and characterized (14,18,23,(30)(31)(32)(33), but the aniline oxidation mechanisms have not been elucidated, that is, the concrete functions of the products of the AD genes in aniline oxidation are unknown. All the AD gene clusters found so far encode GS-like and GAT-like proteins, which have not been found in other dioxygenases, with one exception (34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SRS16, shown to be induced by 3,4-dichloroaniline (3,4-DCA) (5), we also named the operon on pWDL7:rfp and NB8c dca. It was previously shown that aniline dioxygenases consist of multiple components: proteins homologous to glutamine synthetase, glutamine amidotransferase, large and small subunits of the terminal dioxygenase, and a reductase (18,30). In P. putida UCC22 and Delftia tsuruhatensis AD9, where these systems were first described, these components are encoded by, respectively, tdnQ-tadQ, tdnT-tadT, tdnA1-tadA1, tdnA2-tadA2, and tdnB-tadB (18,30).…”
Section: Resultsmentioning
confidence: 99%